Can it define what is content from the information management? - Serna M., Edgar; Guevara C., Roberto; Serna A., Alexei (Revista General de Información y Documentación, 2017)
In a world where everything is apparently content, really grabs attention how little is known and acknowledged about the meaning of this term from the information management. For this reason, many researchers ask themselves what a content is, and they have good reasons for that because everywhere people talk about the management of contents, content development, and content strategies, but unanimous criteria have not been achieved. In this article, a reflection on this subject is made and a definition for this term is proposed, also is proposed a classification based on its specific objective. Some features that necessarily must meet a good content and a good content creator are described.
Keywords: Information; Documentation; Information management; Interactivity; Social networking.